Influence of the Consideration of Future Consequences on Financial Behavior: The Case of Japanese Individual Investors - Toru Suehiro; Koichi Takeda; Takashi Kozu; Toshihiko TAKEMURA (Journal of Economics and Behavioral Studies, 2019)
We analyze the impact of the “consideration of future consequences” (CFC) on the amount of financial assets and the liabilities of individual investors by applying a Tobit model to data from a web-based survey. We find that impatient individuals with high CFC have fewer deposits and financial asset balances. We also examine the influence of the CFC-immediate (CFC-I) and CFC-future (CFC-F) sub-indicators often used in psychology as well as CFC on financial asset balances and liabilities. CFC-I show concern with immediate consequences and also an index related to ego depletion. We find that the higher the CFC-I, the lower the amount of deposits and financial asset balances. However, CFC-F is a sub-indicator designating lack of concern with future consequences; thus, the higher the CFC-F, the larger the debt.